Hubungan Merokok dengan Hasil Pemeriksaan Bakteriologis Sputum pada Pasien Tuberkulosis Paru Kategori I di Puskesmas Teladan Kota Medan Tahun 2017 - Rahmayuli, Putri; Lubis, Debby Mirani (Universitas Muhammadiyah Sumatera Utara, 2018)
Abstract: Tuberculosis is a contagious disease caused by the bacterium Mycobacterium tuberculosis. Most of Mycobacterium tuberculosis bacteria attack the lungs, but can also affect other organs. Smoking is one that increases the risk of pulmonary tuberculosis. The number and duration of active smoking has an effect on the risk of infection and the development of Tuberculosis. The objective of this study was to find out the correlation between smoking and sputum bacteriological examination in Category I pulmonary TB patients at Puskesmas Teladan Medan City 2017. The methods is analytic with cross sectional design. The sample of this research is total sampling from all data of medical record at Puskesmas Teladan which is 30 respondents. The analytical method used is chi-square. The result of the study showed that Category I pulmonary TB patients with smoking habit were 11 people (36.7%), and chi-square analysis showed significance value p = 0,000. The conclusion there was a correlation between smoking and bacteriological sputum examination in Category I pulmonary TB patients.Key word: Smoking, Bacteriological Sputum, Pulmonary Tuberculosis